Relaxation Therapy on Fetal Outcomes in Complicated Pregnancies Suffering Sleep Disorders: A Randomized Clinical Trial - azar nematollahi; Farideh Vaziri; Nasrin Asadi; Mona Doracvandi; Mehrab Sayadi (Shiraz University of Medical Sciences, 2016)
Background: Sleep disorders like snoring, mouth breathing, and insomnia are frequent in pregnancy and studies have shown that poor sleep is linked to obstetric complications. Muscle relaxation technique is an effective method used for improving sleep quality. The purpose of this study was to determine the effect of muscle relaxation technique on fetal outcomes in complicated pregnancies with sleep disorders. Methods: This study was performed as a clinical trial on 160 pregnant women who suffered from preeclampsia and gestational diabetes. The participants filled the Pittsburgh Sleep Quality Index (PSQI) in order to measure the quality and patterns of their sleep. The participants with the total score of 5 or more were included in the present study. Intervention group were asked to use muscle relaxation technique twice a week at home for 8 weeks alongside the routine care. Study variables included sleep quality, Apgar scores, birth weight, levels of Interleukin- 6 (IL- 6), as well as umbilical cord PH and PO2. Results: The mean score of PSQI before the intervention was 9.28±4.16 and 9.18±3.06 in the intervention and control groups without a significant difference (P=0.6), respectively. However, PSQI global score of the experimental group was smaller than the control group at the end of the study (P<0.001). Also, birth weight (P=0.04), Apgar score (P=0.01), and umbilical cord blood po2 (P=0.03) and PH (P=0.01) were higher, and IL-6 (P=0.04) was smaller in the experimental group compared to the control group. Conclusion: The results of this study showed that muscle relaxation, as a simple, inexpensive and safe method, can improve the fetal outcomes such as birth weight, Apgar score, cord blood po2, and cord blood PH, and also it leads to lower IL-6 in complicated pregnancies.